The role of teachers (de-)motivational styles on students' autonomous motivation in physical education and leisure time - Henri Tilga; Kaija Vahtra; Andre Koka (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2023)
Introduction: The aim of this research was to examine the relationships of four perceived teaching styles (i.e., autonomy support, structure, control, and chaos) of physical education (PE) teachers with students' satisfaction of psychological needs as well as autonomous and controlled motivation towards physical activity in PE and leisure time context. Materials and Methods: 320 students (166 boys and 154 girls) aged from 12 to 18 years old (M = 14.13, SD = 1.6) participated in the study. In this cross-sectional study, participants filled in a questionnaire of study variables. A variance-based structural equation model was employed to test the study hypotheses. Results: Autonomy support is indirectly related to students' autonomous motivation towards physical activity in leisure time via satisfaction of a psychological need and autonomous motivation for PE (β = 0.18, p < 0.01). Structuring the teaching style is indirectly related to students' autonomous motivation towards physical activity in leisure time via satisfaction of a psychological need and autonomous motivation for PE (β = 0.21, p < 0.01). Conclusions: When a PE teacher employs an autonomy-supportive and structuring teaching style, it is likely to satisfy students' psychological needs and increase autonomous motivation towards physical activity in PE, which, in turn, may enhance autonomous motivation towards physical activity during leisure time.